New Plants for Florida: Peanut - Don Maynard; Richard L. Jones; Mary Duryea; Berry J. Treat (EDIS, 2003)
The peanut originated in South America, and today it is widely grown for oil, roasted nuts, peanut butter and other products. Research on peanut breeding at FAES dates back to 1920. This document is part of Circular 1440, a publication of the Florida Agricultural Experiment Station, the Agronomy Department and IFAS Communication Services, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date August 2003. Originally published as a booklet by IFAS Communication Services June 2003.